HUBUNGAN ANTARA KEPATUHAN TERAPI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK - MOHAMAD AGUS TIAR (LPPMK STIKES Widyagama Husada, 2022)
ABSTRACT Hemodialysis undertaken by patients can maintain survival while changing the patient's lifestyle. Adherence in hemodialysis is very necessary to maintain life. The purpose of this study was to determine the correlation between adherence to hemodialysis and quality of life in hemodialysis patients at Dr. Saiful Anwar Malang. This research is a descriptive analytic correlative research design with a cross sectional method approach. The sample in this study were 37 CKD patients who underwent hemodialysis in the Malahayati Hemodialysis Room, RSUD Dr. Saiful Anwar Malang. There is a relationship between the level of compliance and the level of quality of life of chronic kidney failure patients undergoing hemodialysis in the Hemodialysis Room of RSUD Dr. Saiful Anwar Malang (p value= 0.005). The relationship is positive by 0,451, the more positive the patient's compliance, the higher the quality of life of chronic kidney failure patients undergoing hemodialysis in the Hemodialysis Room of RSUD Dr. Saiful Anwar Malang. Keywords : Chronic Kidney Failure, Hemodialysis, Adherence, Quality of Life